2011
DOI: 10.1007/s12192-010-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant activity of GP96 C-terminal domain towards Her2/neu DNA vaccine is fusion direction-dependent

Abstract: The Her2 is one of tumor-associated antigens (TAA), regarded as an ideal target of immunotherapy. DNA encoding full-length or truncated rat Her2/neu have shown protective and therapeutics potentials against Her2/neuexpressing mammary tumors. However, the efficacy of active vaccination is limited since Her2 is a self-tolerated antigen. Hence, new strategies are required to enhance both the quality and quantity of the immune response against Her2-expressing tumors. Many studies have used Her2/neu gene with cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The dose and orientation of the antigen towards HSP in the fusion gene may have clinical implications for the design and optimization of HSP‐based vaccines [21, 29, 55, 56]. Regarding to the previous studies, the increasing amount of N‐terminal fragment of gp96 leads to rise in the percentage of the peptide‐specific T cells responses [21].…”
Section: Discussionmentioning
confidence: 99%
“…The dose and orientation of the antigen towards HSP in the fusion gene may have clinical implications for the design and optimization of HSP‐based vaccines [21, 29, 55, 56]. Regarding to the previous studies, the increasing amount of N‐terminal fragment of gp96 leads to rise in the percentage of the peptide‐specific T cells responses [21].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies demonstrate that the use of GRP94 as an antitumor vaccination can prevent cancer development. However, GRP94 vaccination in mice appears less promising in the treatment of established tumors 114,116,117 , and clinical trials across various types of tumors suggest that autologous tumor-derived GRP94 vaccination may have limited efficacy 118121 .…”
Section: The Role Of Grp94 and Other Chaperones In Antitumor Vaccinationmentioning
confidence: 99%
“…It has been shown that interaction of anti-CD4-binding site (CD4bs) Abs with HIV-1 gp120 induces conformation changes that lead to enhanced antigenicity and immunogenicity of neutralizing epitopes in the V3 loop and C1 regions of gp120 of several subtypes and the immune complexes as immunogens induced serum Abs to gp120 and V3 at significantly higher titers than those induced by the respective uncomplexed gp120s [377]. Fusion of the c-terminal domain of gp96 to transmembrane and extracellular domain of rat Her2/neu enhanced the immunogenicity of Her2/neuIt DNA vaccine [378]. It is possible that such an immunogenicity enhancement is due to increased rigidity of the protein antigen.…”
Section: Specific Peptides/proteinsmentioning
confidence: 99%